2020
DOI: 10.1111/jbi.14040
|View full text |Cite
|
Sign up to set email alerts
|

Vicariance and regionalization patterns in snakes of the South American Atlantic Forest megadiverse hotspot

Abstract: Aim Vicariance has often been invoked to explain bioregionalization patterns in the Neotropics. Using a revised point locality data for endemic species, we aimed to test for the first time the predictions of the vicariance model in shaping biogeographical regions for endemic snakes in the Atlantic Forest (AF) megadiverse hotspot. Location South American Atlantic Forest. Taxon Snakes (Reptilia, Serpentes). Methods To identify the non‐random groups of co‐distributed species, we mapped 21,101 point locality recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Thus, a myriad of processes might have shaped their current diversity and geographic patterns. Despite the great endemism and diversity of this group in the Neotropical region [51], it is only recently that the biogeographic processes responsible for this diversity have started to be studied [52][53][54][55]. Snakes of the family Viperidae, also known as vipers, are distributed worldwide and comprise approximately 360 species [56].…”
Section: Plos Onementioning
confidence: 99%
“…Thus, a myriad of processes might have shaped their current diversity and geographic patterns. Despite the great endemism and diversity of this group in the Neotropical region [51], it is only recently that the biogeographic processes responsible for this diversity have started to be studied [52][53][54][55]. Snakes of the family Viperidae, also known as vipers, are distributed worldwide and comprise approximately 360 species [56].…”
Section: Plos Onementioning
confidence: 99%
“…Six centers of endemism or biogeographic subregions are currently known for snakes in the Atlantic Forest (Moura et al 2017;Barbo et al 2021), and the PEC is always recovered even with different methodologies. The PEC forests represent the northernmost center of endemism and the only one with a strong connection and geographical proximity with the Caatinga (Pereira- , assigning a very particular snake fauna to this region.…”
Section: Species Richness and Sampling Biasmentioning
confidence: 99%
“…According to Nogueira et al (2019), there are 415 species of snakes in Brazil, and approximately 220 in the Atlantic Forest, representing 54.32% of all species (Moura et al 2017;Barbo et al 2021). A total of 86 species are recorded in the PEC, representing 43.09% of all species recorded in the Atlantic Forest.…”
Section: Species Richness and Sampling Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…The Atlantic Forest is a complex morphoclimatic domain, including different ecological constraints and conditions throughout its range ( Olson et al 2001 ; Carnaval et al 2014 ). This region harbors a very diverse and highly endemic snake fauna, with at least 252 species, including 79 endemic snakes ( Barbo et al 2021 ). Carnaval et al (2014) demonstrated that climate variation affects the geographical distribution of endemic vertebrates in the Atlantic Forest, including amphibians, lizards, snakes, and Passeriformes.…”
mentioning
confidence: 99%